Observational study on the current status of thalassaemia in Malaysia: a report from the Malaysian Thalassaemia Registry - Hishamshah Mohd Ibrahim; Zulaiha Muda; Ida Shahnaz Othman; Mohamed Najib Mohamed Unni; Kok Hoi Teh; Asohan Thevarajah; Kogilavani Gunasagaran; Gek Bee Ong; Seoh Leng Yeoh; Aisyah Muhammad Rivai; Che Hadibiah Che Mohd Razali; Nazzlin Dizana Din; et al. (BMJ Open)
Objective Thalassaemia is the most common inherited blood disorder in Malaysia. This study aims to report the current status of thalassaemia in Malaysia and provide a comprehensive understanding of the disease through data obtained from the Malaysian Thalassaemia Registry.Design Data were extracted from the Malaysian Thalassaemia Registry, a web-based system accessible to enrolled users through www.mytalasemia.net.my.Setting The Malaysian Thalassaemia Registry data was recorded from reports obtained from 110 participating government and university hospitals in Malaysia.Participants The patients were those attending the 110 participating hospitals for thalassaemia treatment.Intervention Data were collected from the Malaysian Thalassaemia Registry from 2007 until the fourth quarter of 2018.Primary outcome measure 7984 out of 8681 patients with thalassaemia registered in the Malaysian Thalassaemia Registry were reported alive.Results Majority of the patients were reported in the state of Sabah (22.72%); the largest age group affected was 5.0–24.9 years old (64.45%); the largest ethnic group involved was Malay (63.95%); and the major diagnosis was haemoglobin E/β-thalassaemia (34.37%). From the 7984 patients, 56.73% were on regular blood transfusions and 61.72% were on chelation therapy. A small fraction (14.23%) has undergone splenectomy, while the percentage of patients with severe iron overload (serum ferritin ≥5000 µg/L) reduced over time. However, cardiac complications are still the main cause of death in patients with thalassaemia.Conclusion Data gathered into the registry can be used to understand the progression of the disorder, to monitor iron overload management and to improve the outcomes of treatment, to enhance preventive strategies, reduce healthcare burden and improve the quality of life. Sustainability of the Malaysian Thalassaemia Registry is important for surveillance of thalassaemia management in the country and help the national health authorities to develop more effective policies.